HDI XMAS July 15, 2019. Christine Sooley photos. - Barrett, Terra (1985)
A photo of Daphne Jackson, Carl Sooley, Christine Sooley, Donna Sooley, and Wilfred Jackson sitting together in front of a fireplace in Heart's Delight.